Edukasi Penggunaan Obat yang Aman saat Berpuasa: Meningkatkan Kesadaran Masyarakat di Desa Binaan Fakultas Farmasi dan Sains UHAMKA - Siska, Siska; Dwitiyanti, Dwitiyanti; Sunaryo, Hadi; Widayanti, Ari; Wardani, Elly; Prisiska, Fahjar (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Fasting during Ramadan is an obligatory act of worship for Muslims, but for individuals with certain health conditions, fasting while undergoing drug therapy can be confusing. This community service activity (PKM) aims to provide education to the community on the correct way to consume drugs while fasting. This activity was carried out in the Foster Village of the Faculty of Pharmacy and Science UHAMKA, Bintara RT 007, Bekasi City, West Java. This activity involved three pharmacists as speakers. The methods used for implementing community service activities include lectures, question and answer sessions, and interactive discussions. The results of community service from the activity showed a significant increase in community knowledge about the correct use of drugs during fasting. This PKM is expected to increase public awareness and understanding of the correct use of drugs, so that they can carry out fasting more optimally and safely.